ANALISIS KESERASIAN PROGRAM LAYANAN BUSINESS DEVELOPMENT SERVICE â PROVIDER (BDS-P) DENGAN PERATURAN PEMERINTAH TERKAIT PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI JAWA TIMUR - fatoni, Irfan; Nurhayati, Indah Dewi (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The aim of the study to analyze the extent to which the harmony between programming services owned by BDS-P with applicable government regulation and associated with the development of SMEs in East Java. Research subjects in this study were BDS-P (Business Development Services Provider) that is a profession that provides various forms of service/services to clients engaged in business development. While the object of this research is a service/services provided by BDS-P to the client. In this study HOQ matrix to facilitate the measure of harmony. The study says that, the program services of the BDS-P in Korda Bojonegoro has had a good harmony. Korda Surabaya require efforts to improve compatibility. Korda Madura has been able to achieve full harmony. Korda Jember harmony rate is among the lowest compared to other cord-cord. Korda Malang has the highest level of compatibility as compared to other cord. Korda Kediri showed that the harmony of the BDS-P in cord still needs to be improved. Korda Madiun including that need attention compared with other cords. Keywords: Business Development ServicesâProvider, government policie, SME